Investigation of the relationship between hospitalization periods in patients with acute coronary syndrome (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the relationship between high sensitivity C-reactive protein (HsCRP), cardiac markers, D-dimer and brain natriuretic peptide (BNP) measured at admission to the emergency department in patients with acute coronary syndrome (ACS).Material and Methods: In our clinic, patient records were scanned backwards. The records of the patients who presented to the emergency department with chest pain were evaluated. Patients with acute coronary syndrome were included in the study. Laboratory values, echocardiogram and electrocardiograms of these patients were examined.Results: 88 patients with acute coronary syndrome were included in our study. According to the complaints of the patients, 93.2% (n=82) had chest pain, 45.5% (n=40) sweating, and 42% (n=37) had left arm pain at their admission to the emergency unit. The mean stick blood glucose value of the patients who came to our emergency department was 157±75.38 mg / dl (37.00-524.00 mg / dl). Biochemical laboratory values measured from venous blood taken at the time of arrival of patients, mean HsCRP 11.67±15.4 mg / l, insulin 14.87±29.53 IU / ml, glucose level 139.11±74.3 mg / dl, CK 426.9±12x8.9 mg / dl and CK-MB were determined as 41.1±46.8 mg / dl.Conclusion: We conclude that there is no correlation between cardiac parameters, DDIM, glucose, insulin and HsCRP levels in the in-hospital prognosis and there is a relationship between the measured BNP levels and the length of hospital stay.Keywords: Emergency service; trauma; blood glucose; DDIM.